2016
DOI: 10.1186/s13014-016-0600-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity in comprehensive head and neck radiation for nasopharynx and paranasal sinus cancers: cohort comparison of 3D conformal proton therapy and intensity modulated radiation therapy

Abstract: BackgroundTo evaluate acute toxicity endpoints in a cohort of patients receiving head and neck radiation with proton therapy or intensity modulated radiation therapy (IMRT).MethodsForty patients received comprehensive head and neck radiation including bilateral cervical nodal radiation, given with or without chemotherapy, for tumors of the nasopharynx, nasal cavity or paranasal sinuses, any T stage, N0-2. Fourteen received comprehensive treatment with proton therapy, and 26 were treated with IMRT, either compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…Without IMPT to treat skin as an avoidance structure, it will receive the full prescription dose, resulting in higher cutaneous toxicity in patients treated with proton‐based versus photon‐based treatments. Prior studies also have reported decreased acute toxicity with PT compared with IMRT . Late grade 3 toxicities were seen in only 6 patients (7% of our entire cohort), and included vision loss, osteonecrosis with soft tissue necrosis requiring surgical debridement and flap reconstruction, brain necrosis, soft tissue fibrosis, and severe facial pain requiring hospitalization.…”
Section: Discussionmentioning
confidence: 60%
“…Without IMPT to treat skin as an avoidance structure, it will receive the full prescription dose, resulting in higher cutaneous toxicity in patients treated with proton‐based versus photon‐based treatments. Prior studies also have reported decreased acute toxicity with PT compared with IMRT . Late grade 3 toxicities were seen in only 6 patients (7% of our entire cohort), and included vision loss, osteonecrosis with soft tissue necrosis requiring surgical debridement and flap reconstruction, brain necrosis, soft tissue fibrosis, and severe facial pain requiring hospitalization.…”
Section: Discussionmentioning
confidence: 60%
“…One comparison of 3D and IMRT approaches showed that IMRT for oral cancer could reduce the volumes of mandible that received >50 Gy, >55 Gy, and >60 Gy, in addition to producing fewer hot spots and a lower maximum dose to the mandible [10]. More recently, numerous reports have been published documenting the theoretical advantages of proton therapy over photon therapy for head and neck cancer [2325]. The first use of multi-field optimization for IMPT was reported in 2014 for head and neck malignancies [16]; indeed, IMPT (as opposed to passively scattered proton therapy) has been shown in treatment-planning comparisons to be the most effective in reducing the doses to the spinal cord, parotid, and brainstem [13, 26].…”
Section: Discussionmentioning
confidence: 99%
“…A recent MD Anderson Cancer Center series compared intensity-modulated proton therapy (IMPT) to intensity-modulated radiation therapy using photons for nasopharyngeal cancer and found a 3-fold reduction in the rate of gastrostomy tube placement for patients receiving protons, which was attributed to decreased oral cavity toxicity [2]. Additional studies evaluating the use of protons in head and neck cancer have yielded similar conclusions [3][4][5][6].…”
Section: Introductionmentioning
confidence: 97%